Stability and Bifurcation of a Class of Discrete-Time Cohen-Grossberg Neural Networks with Delays - Qiming Liu; Rui Xu; Zhiping Wang (Discrete Dynamics in Nature and Society)
A class of discrete-time Cohen-Grossberg neural networks with delays is investigated in this paper. By analyzing the corresponding characteristic equations, the asymptotical stability of the null solution and the existence of Neimark-Sacker bifurcations are discussed. By applying the normal form theory and the center manifold theorem, the direction of the Neimark-Sacker bifurcation and the stability of bifurcating periodic solutions are obtained. Numerical simulations are given to illustrate the obtained results.